The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/cancers13133369
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Treatment Response of Double Expression of MYC and BCL2 in Patients with Diffuse Large B-Cell Lymphoma: A Systematic Review and Meta-Analysis

Abstract: MYC/BCL2 protein co-expression (i.e., double expressor) has been shown to be a negative predictor of outcome in diffuse large B-cell lymphoma (DLBCL). We aimed to establish the incidence of double expressor status in patients with de novo DLBCL and identify the predictive value of this biomarker on treatment response through systematic review and meta-analysis. PubMed and Embase were searched for studies published through December 2019 that reported proportions of double expressor DLBCL. The pooled proportions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 82 publications
0
8
1
Order By: Relevance
“…An MYC expression was detected in 23.4% of HIV‐associated DLBCL, and 13% were DE, most of them of the non‐GC phenotype. This incidence is slightly lower than that reported in DLBCL series of immunocompetent patients (20–30%) 14,55–57 . Of note, MYC positivity tended to be associated with worse PFS, and DE was significantly associated with shorter probability of OS and PFS.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…An MYC expression was detected in 23.4% of HIV‐associated DLBCL, and 13% were DE, most of them of the non‐GC phenotype. This incidence is slightly lower than that reported in DLBCL series of immunocompetent patients (20–30%) 14,55–57 . Of note, MYC positivity tended to be associated with worse PFS, and DE was significantly associated with shorter probability of OS and PFS.…”
Section: Discussioncontrasting
confidence: 55%
“…This incidence is slightly lower than that reported in DLBCL series of immunocompetent patients (20–30%). 14 , 55 , 56 , 57 Of note, MYC positivity tended to be associated with worse PFS, and DE was significantly associated with shorter probability of OS and PFS. These results support the consideration, made in general DLBCL, that MYC and BCL2 coexpression, but not MYC expression alone, is associated with a worse prognosis.…”
Section: Discussionmentioning
confidence: 95%
“…The association of DEL and inferior survival ( p = .001) was the anticipated result because many trials have shown it before 35–37 . The need and the benefit of treatment intensification in DEL/DHL patients was demonstrated in retrospective trials.…”
Section: Discussionmentioning
confidence: 94%
“…The association of DEL and inferior survival ( p = .001) was the anticipated result because many trials have shown it before. 35 , 36 , 37 The need and the benefit of treatment intensification in DEL/DHL patients was demonstrated in retrospective trials. In trial by Lansburg et al, 38 patients with intensive (DA‐EPOCH‐R, R‐HyperCVAD, R‐CODOX‐M/IVAC) ICT experienced superior rates in 3‐year RFS, compared with R‐CHOP (75% vs. 51% respectively, p = .003).…”
Section: Discussionmentioning
confidence: 99%
“…In the following years, the number of researches that do not favor therapy intensification for patients with DEL [29][30][31] notably outnumbered those who do favor intensification [32]. Systematic review and meta-analysis by Hwang et al [33], that included 7054 patients from 41 studies, confirmed that CR rate is significantly lower in newly diagnosed DEL than non-DEL DLBCL patients. However, one of the main limitations of the study was its inability to compare different treatment approaches and CR rates due to insufficient data.…”
Section: Clinical Implication Of Double Expressor Lymphomas and Treat...mentioning
confidence: 99%